Callicarpa japonica Thunb. attenuates cigarette smoke-induced neutrophil inflammation and mucus secretion. (4th December 2015) - Lee, Jae-Won; Shin, Na-Rae; Park, Ji-Won; Park, So-Yeon; Kwon, Ok-Kyoung; Lee, Han-Sol; Hee Kim, Jung; Lee, Hee Jae; Lee, Joongku; Zhang, Zhi-yun; Oh, Sei-Ryang; Ahn, Kyung-Seop
Abstract: Ethnopharmacological relevance: Callicarpa japonica Thunb. (CJT) is traditionally used as an herbal remedy for the treatment of inflammatory diseases in Korea, China, and Japan. In this study, we evaluated the effects of C. japonica Thunb. (CJT) on the development of COPD using a Cigarette smoke (CS)-induced murine model and cigarette smoke condensate (CSC)-stimulated H292 cells, human pulmonary mucoepidermoid cell line. Material and methods: C. japonica Thunb. was isolated from the leaves and stem of C. japonica. The methanol extract profile was obtained by UPLC Q-TOF-MS analysis. In in vivo experiment, the mice received 1 h of cigarette smoke for 10 days. C. japonica Thunb. was administered to mice by oral gavage 1 h before cigarette smoke exposure for 10 days. In in vitro experiment, we evaluated the effect of C. japonica Thunb. on the expression of MUC5AC and proinflammatory cytokines in H292 cells stimulated with CSC. Results: CJT treatment effectively suppressed the infiltration of neutrophils, and decreased the production of ROS and the activity of neutrophil elastase in the bronchoalveolar lavage fluid (BALF) induced by CS. CJT also significantly attenuated production of proinflammatory cytokines such as IL-6 and TNF-α in the BALF, and reduced the infiltration of inflammatory cells and the production of mucus in lung tissue induced by CS. In in vitro experiments, CJT decreased the expression of MUC5AC and proinflammatory cytokines in CSC-stimulated H292 cells. Furthermore, CJT attenuated the phosphorylation of ERK induced by CSC in H292 cells. Taken together, CJT effectively reduced the neutrophil airway inflammation and mucus secretion induced by CS in murine model, and inhibited the expression of MUC5AC in CSC-stimulated H292 human lung cell line. These findings suggest that CJT has a therapeutic potential for the treatment of COPD. Graphical abstract: